Profit-Sharing Wages and Income Equity in the Informal Barbershop Sector: An Islamic Economics Perspective - Abustan Nur; Ulil Albab (Jurnal Internasional Ekonomi Islam, 2026)
Objective: This study examines the implementation of a profit-sharing wage system in informal barbershop businesses in Watampone City and analyzes its implications for income equity and labor relations from an Islamic economics perspective. Method: This research uses a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed descriptively using the framework of Islamic economics and distributive justice. Result: The findings show that profit-sharing wages are considered relatively fair because income is distributed proportionally according to workers’ contributions and business performance. The system enhances work motivation and strengthens partnership-based labor relations. However, income instability and the absence of written contracts remain important challenges. Although the principles of tarāḍī (mutual consent) and transparency are generally upheld, the lack of formal akad documentation reduces contractual clarity. It increases the potential for gharar, indicating that Sharia compliance is not yet fully achieved in procedural terms.  Implication: This study suggests that profit-sharing wage systems can serve as an alternative mechanism to promote distributive justice, flexibility, and harmonious labor relations in the informal sector. It also highlights the importance of strengthening contractual documentation to improve Sharia compliance. Originality or Novelty: This study contributes to Islamic economics literature by providing empirical evidence from the informal personal service sector, particularly barbershop businesses, and by proposing a contextual model that integrates Sharia principles with practical wage arrangements.